REAL EARNINGS MANAGEMENT SEBAGAI PREDIKTOR RASIO PEMBAYARAN DIVIDEN DAN IMPLIKASINYA TERHADAP NILAI PERUSAHAAN - Diasari, Putu Sinta Ayu; Suaryana, I Gusti Ngurah Agung (Jurnal Ilmiah Akuntansi dan Bisnis, 2014)
ABSTRACT Real earnings management is one of important issue in earnings management activity. This study was to examine the influence of  real earnings management on firm’s value through dividend payout ratio (DPR) as intervening variable. The result of path analyst was an increase in real earnings management would decrease firm’s value. Real earnings management did not influence dividend payout ratio. Dividend payout ratio did not influence firm’s value. Dividend payout ratio (DPR) was not an intervening variable, because there was no influence of real earnings management to firm’s value through dividend payout ratio. Keywords : earnings management, DPR, firm’s values